FDI and innovation dynamics: The role of foreign corporate groups and technological pathways in domestic green innovation - Francesca Micocci; Mahdi Ghodsi; Armando Rungi (The Vienna Institute for International Economic Studies (wiiw), 2025)
This paper investigates how the presence of foreign direct investment (FDI) contributes to domestic innovation with a focus on green technologies in the European regions between 2013 and 2018. Using a rich dataset combining patent data, firm-level data and FDI proxies, we identify a clear pattern: when foreign investors are technologically sophisticated, domestic firms in the regions where they invested show a higher propensity for patenting. The patenting activity by the parent companies of multinational enterprises (MNEs) and their corporate perimeter plays a more crucial role than local foreign subsidiaries. Furthermore, we find that the technological focus of MNEs - green vs. non-green - shapes the direction of these spill-overs. Notably, we provide novel evidence of linkages between the green patenting activity of MNE parents located abroad and the green innovation of domestic firms in the European Union, mediated through foreign subsidiaries operating in close proximity. Policy efforts aiming to foster green innovation should therefore prioritise attracting foreign investors with strong innovation records in environmentally sustainable technologies.
Keywords: O32; F23; O34; L23; 330; technological spill-overs; multinational enterprises; FDI; domestic innovation; firm-level data